African town eaudiobook - Waters, Charles (Listening Library, 2022)
Chronicling the story of the last Africans brought illegally to America in 1860, African Town is a powerful and stunning novel-in-verse. In 1860, long after the United States outlawed the importation of enslaved laborers, 110 men, women and children from Benin and Nigeria were captured and brought to Mobile, Alabama aboard a ship called Clotilda . Their journey includes the savage Middle Passage and being hidden in the swamplands along the Alabama River before being secretly parceled out to various plantations, where they made desperate attempts to maintain both their culture and also fit into the place of captivity to which they'd been delivered. At the end of the Civil War, the survivors created a community for themselves they called African Town, which still exists to this day. Told in 14 distinct voices, including that of the ship that brought them to the American shores and the founder of African Town, this powerfully affecting historical novel-in-verse recreates a pivotal moment in US and world history, the impacts of which we still feel today. * This audiobook includes a downloadable PDF with a glossary and additional resources.